Determinan Minat Individu Melakukan Transaksi Berbasis Online - Aisyah, Intan; Baridwan, Zaki (Jurnal Ilmiah Mahasiswa FEB, 2014)
The objective of this research is to examine factors that influence individualintention of doing online transactions. This research is a combination of variables from the researches done by Xu (2000) and Barnes (2014), which used the model of Theory of Reasoned Actions (TRA) as the basis of their researches. This research used survey method to collect data. Samples of this research were female students of Accounting in Economics and Business Faculty Brawijaya University who had ever done online transactions. A total of 156 data can be analyzed by using SmartPLS software. The result of this result shows that attitude, subjectivenorms, personality traits and perceived privacy have significant effect toindividual intention of doing online transactions. Whereas perceived security has no significant influence to individual intention of doing online transactions. It means that individual intention of doing online transactions is influenced by attitude, subjective norms, personality traits and perceived privacy. The implication of this research is relevant for management of the company that concern about online transactions to consider the attitude, subjective norns, personality traits and perceived privacy in applying and developing their online transaction system.Keywords: Theory of Reasoned Actions (TRA), online transactions, intention, attitude, subjective norms, personality traits, perceived security,perceived privacy